PERIPHERAL ISLAM: A Critique of the Epistemic Marginalization of Southeast Asian Islam - Hanafi, Imam; Maulana, Maulana (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This paper examines the phenomenon of